1991
DOI: 10.1136/thx.46.3.160
|View full text |Cite
|
Sign up to set email alerts
|

Bone turnover during high dose inhaled corticosteroid treatment.

Abstract: This study was performed to determine the effects of high doses of two inhaled corticosteroids, beclomethasone dipropionate and budesonide, on biochemical indices of bone turnover (urinary hydroxyproline:creatinine and calcium: creatinine ratios, plasma alkaline phosphatase, and parathyroid hormone). Twelve healthy male doctors, aged [25][26][27][28][29][30][31][32][33][34][35][36]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
3
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(67 citation statements)
references
References 20 publications
(1 reference statement)
5
56
3
3
Order By: Relevance
“…Only in the study of A li et al were changes found [32]. In this study in 8 healthy volunteers, a small decrease in AP was found after treatment with BDP 2.0 mg/day for 4 weeks, whereas after BUD 1.8 mg/day (n -8) no changes were observed.…”
Section: Side-effects: General Considerationscontrasting
confidence: 55%
See 1 more Smart Citation
“…Only in the study of A li et al were changes found [32]. In this study in 8 healthy volunteers, a small decrease in AP was found after treatment with BDP 2.0 mg/day for 4 weeks, whereas after BUD 1.8 mg/day (n -8) no changes were observed.…”
Section: Side-effects: General Considerationscontrasting
confidence: 55%
“…Markers of bone resorption, such as excretion of calcium and hydroxyprolines in urine, appeared to be increased in one study [32], but were unaltered in most studies [21,25,26,30,31,33,37]. Other markers of bone resorption include type 1 carboxy-terminal telopeptide (1CTP) and (deoxy)pyridinoline cross links [34,39].…”
Section: Biochemical Markers O F Bone Turnovermentioning
confidence: 99%
“…En pacientes asmáticos tratados con esteroides inhalados se ha notificado una disminución de la formación ósea por la reducción del PICP. 28 Kerstjens y colaboradores 10 no comunican diferencias en este marcador, mientras que Crowley y colaboradores 23 informan niveles elevados de PICP y sugieren que los glucocorticoides modifican el aclaramiento del mismo.…”
Section: Discussionunclassified
“…Estes esteróides podem estimular a reabsorção óssea diretamente ou ainda indiretamente, através do aumento na secreção do PTH (54). O aumento na excreção urinária de metabólitos de degradação do colágeno (hidroxiprolina, deoxipiridinolina, e telopeptídeos N e C terminal de colágeno tipo I) é uma evidência bioquímica do incremento de reabsorção óssea induzida pelos glicocorticóides (55)(56)(57).…”
Section: Iii) Ação Direta Nas Células óSseasunclassified